Role of Aldosterone and Mineralocorticoid Receptor in Cardiovascular Aging - Gorini, Stefania; Kim, Seung Kyum; Infante, Marco; Mammi, Caterina; La Vignera, Sandro; Fabbri, Andrea; Jaffe, Iris Z.; Caprio, Massimiliano (Frontiers in Endocrinology, 2019)
The mineralocorticoid receptor (MR) was originally identified as a regulator of blood pressure, able to modulate renal sodium handling in response to its principal ligand aldosterone. MR is also expressed in many tissues other than kidney, including the heart, vasculature and adipose tissue. More recent studies have shown that extra-renal MR plays a relevant role in the control of cardiovascular and metabolic functions and has recently been implicated in the pathophysiology of aging. MR activation promotes vasoconstriction and acts as a potent pro-fibrotic agent in cardiovascular remodelling. Aging is associated with increased arterial stiffness and vascular tone, and modifications of arterial structure and function are responsible for these alterations. MR activation contributes to increase blood pressure with aging by regulating myogenic tone, vasoconstriction, and vascular oxidative stress. Importantly, aging represents an important contributor to the increased prevalence of cardiometabolic syndrome. In the elderly, dysregulation of MR signalling is associated with hypertension, obesity and diabetes, representing an important cause of increased cardiovascular risk. Clinical use of MR antagonists is limited by the adverse effects induced by MR blockade in the kidney, rising the risk of hyperkalaemia in older patients with reduced renal function. Therefore, there is an unmet need for the enhanced understanding of the role of MR in aging and for development of novel specific MR antagonists in the context of cardiovascular rehabilitation in the elderly, in order to reduce relevant side effects.